Caracterização filogenética, biológica e patogênica de espécies do complexo Fusarium solani associadas à podridão do colo do maracujazeiro - Cardoso, Acleide Maria Santos (2015)
Brazil is one of the most important producers of yellow passion fruit (Passiflora edulis f. flavicarpa). However, diseases such as collar rot cause significant reduction in productivity, and result in constant migration of the crop to regions supposedly free of the pathogen. We investigated whether the causal agent of collar rot belongs to a distinct phylogenetic and biological species within the Fusarium solani species complex - FSSC. Ninety eight isolates with morphological characteristics of F. solani were obtained from diseased plants with symptoms of collar rot collected in the nine different states (BA, CE, MG, SP, RJ, GO, PA, MA, and PI). Monospore isolates were subjected to phylogenetic analyses of partial TEF-1α and RPB2 sequences, crossing experiments, pathogenicity tests, and evaluation of morphological markers. Maximum Parsimony analysis of combined TEF-1α and RPB2 sequences grouped the isolates into nine distinct lineages within Clade 3 of the FSSC. Pathogenicity tests revealed that isolates from seven of these lineages caused disease. Two of these lineages are formed by self-fertile (homothallic) isolates, FSSC 21, known as F. striatum, and a new lineage, not yet reported in the literature, preliminarily numbered FSSC 40. The other five lineages with isolates that caused collar rot on Passiflora are FSSC 3+4 (“F. falciforme”), FSSC 20, and FSSC 41, another new lineage not yet reported in the literature. Isolates of opposite mating types from five heterothallic lineages were crossed with isolates of the same lineage, isolates of other lineages, and representatives of known mating populations within the FSSC. Strains of FSSC 3 + 4, FSSC 34 and the new heterothallic lineage FSSC 41 formed fertile perithecia only when crossed with members of the same lineage, supporting their recognition as three distinct biological species. Specific morphological characters could not be assigned to the different phylogenetic lineages identified in association with passion fruit. In conclusion, seven distinct lineages within Clade 3 of the FSSC can cause collar rot of passion fruit, including two new lineages, FSSC 40 and FSSC 41. Other two lineages occur in association with Passiflora, but did not pathogenicity have been studied. These findings will contribute to a more reliable diagnosis of the etiological agent of collar rot. Breeding programs looking for genetic resistance will also benefit from this knowledge about the true diversity of the pathogen.